Connectivity-preserving-based distributed adaptive asymptotically synchronised tracking of networked uncertain nonholonomic mobile robots with actuator failures and unknown control directions. Issue 11 (18th August 2021) - Xu, Yujing; Wang, Chaoli; Yan, Weigang; Lin, Mingfeng; Tao, Jianguo
Abstract : This brief addresses a distributed adaptive asymptotically synchronous tracking problem based on guaranteed connectivity for networked uncertain nonholonomic mobile robots (NMRs) with actuator failures and unknown control directions. First, a radial basis function (RBF) neural network is used to approximate the unknown nonlinear functions, and a distributed nonlinear error surface is introduced to achieve synchronous tracking between NMRs and maintain the initial connectivity patterns. Then, a conditional inequality that allows multiple piecewise Nussbaum functions to achieve robust control is proposed to solve the problem of unknown actuator failures and unknown control directions. Moreover, the proposed protocol ensures that all signals in the closed-loop system are globally bounded and the tracking errors converge asymptotically to zero. Finally, a simulation example verifies the effectiveness of the proposed adaptive laws.